Beauty in the eye of the beholder: Using facial electromyography to examine the association between eating disorder symptoms and perceptions of emaciation among undergraduate women. (June 2017) - Dodd, Dorian R.; Velkoff, Elizabeth A.; Forrest, Lauren N.; Fussner, Lauren M.; Smith, April
Highlights: Emaciated and overweight bodies were perceived negatively among undergraduate women. More negative self-report ratings of overweight bodies related to eating disorder symptoms. Less negative affective reactions to emaciated bodies related to eating disorder symptoms. Psychophysiological research tools provide valuable information beyond self-report data. Abstract: Thin-ideal internalization, drive for thinness, and over-evaluation of the importance of thinness are associated with eating disorders (EDs). However, little research has examined to what extent perceptions of emaciation are also associated with ED symptoms. In the present study, 80 undergraduate women self-reported on ED symptomatology and perceptions of emaciated, thin, and overweight female bodies. While participants viewed images of these different body types, facial electromyography was used to measure activation of facial muscles associated with disgust reactions. Emaciated and overweight bodies were rated negatively and elicited facial responses consistent with disgust. Further, ED symptomatology was associated with pronounced aversion to overweight bodies (assessed via self-report pleasantness ratings), and attenuated negative affect to emaciated bodies (assessed via facial electromyography). The latter association was significant even when controlling for self-reported perceptions of emaciation, suggesting that psychophysiological methods in ED research may provide valuable information unavailable via self-report.